(untitled) (Update Dental College Journal, 2022)
Tooth wear is caused by a variety of reasons, many of which are unknown. Tooth wear management is difficult and complex. For effective treatment, accurate measurement of occlusal vertical dimension (OVD), interocclusal rest space, and centric relation records are required. The analysis of facial soft tissue contours is very crucial. A clinician must remember two things before treating a case with full mouth rehabilitation; severe wear does not always cause loss of OVD and it also does not eliminate all defective occlusal interferences. A systematic method may be beneficial in achieving a predictable and desirable result. This paper describes the step-by-step treatment of a 63-year-old patient who had lost occlusal vertical dimension due to parafunctional habits. Making occlusal overlay bilateral splints in acrylic resin and provisional restorations in mandibular teeth for the healing of the intermaxillary distance was the first strategy for oral rehabilitation. The ultimate rehabilitative therapy evolved into direct composite resin restorations associated with all-ceramic crowns fortified by lithium disilicate after the patient’s adaption and muscle stability to the new occlusal situation. We established that all teeth had solid connections with similar intensity in centric relation, as well as anterior guiding in line with functional jaw movement. Update Dent. Coll. j: 2022; 12(1): 40-44